Religious Moderation Policy: Concept, Implementation, and Challenges in Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia as a multicultural country with religious, ethnic, and cultural diversity faces serious challenges in maintaining social harmony amidst increasing intolerance, extremism, and politicization of religion. In response, the government developed a religious moderation policy to instill just, balanced, and tolerant religious values. However, this policy has not been fully grounded in society, given the gap in understanding between state idealism and the developing social reality. This study aims to analyze the concept, implementation, and structural and cultural challenges in the implementation of religious moderation policies in Indonesia. The method used is a qualitative approach with the Systematic Literature Review (SLR) technique on various relevant national and international scientific publications in the period 2018–2024. The results of the study show that the implementation of this policy is still dominated by a formalistic approach and has not involved active participation from grassroots communities. In addition, ideological resistance, weak public communication, and minimal impact-based evaluation are the main challenges. Therefore, a more participatory, contextual, and local culture-based moderation approach is needed so that this policy does not just become a state project, but a shared life value.